KAOKOXYLON ZALESSKYI (SAHNI) MAHESHWARI (CONIFEROPSIDA), EN EL PÉRMICO SUPERIOR DEL CERRO COLORADO DE LA ANTIGUA, LA RIOJA, ARGENTINA (Ameghiniana, 2014)
An Upper Permian gymnospermous wood from the Cerro Colorado de La Antigua (La Rioja province) is described. It is characterized by a little lobulated heterogeneous parenchymatic/sclerenchymatic pith; the primary xylem has wedge-like projections, and the secondary xylem is of Araucarioxylon type with marked growth rings. It is a "cornplaisant" wood.